Faktor-Faktor yang Mempengaruhi Pendapatan Pedagang di Pasar SanglahSemasa Pandemi Covid-19 - PUSPANINGRUM, NI LUH GEDE ERMA; WIDHIANTHINI, WIDHIANTHINI; SUDARMA, I MADE (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Factors Affecting Traders Income at Sanglah Market During the COVID-19 Pandemic Sanglah Market is a type of traditional market that provides people's daily needs. Judging from the data from the secretariat of traders at Sanglah Market, some traders who sell kiosks or have their licenses revoked because of a decrease in income so that traders find it difficult to pay their obligations. The purpose of this study is to analyze the characteristics of traders, analyze the factors that affect the income of traders and the problems faced by traders at Sanglah Market during the COVID-19 pandemic. The method used is descriptive qualitative and quantitative with SPSS-25 analysis technique. The data used are primary data from the respondents' questionnaires measured by an open scale. The results showed that the characteristics of the dominant traders aged 15-65 years were female, the number of family dependents was 4-6 people and came from the Denpasar area. Capital factors, trading locations and types of merchandise have a positive and significant effect on income. The factor of trading hours has a negative and insignificant effect on the income of traders at Sanglah Market during the COVID-19 pandemic. The problems faced by traders at Sanglah Market during the COVID-19 pandemic were the declining purchasing power of consumers, the decrease in consumer visits to the market, the reduced number of merchandise and the decline in the price of merchandise.